Retinal Targets ALDH Positive Cancer Stem Cell and Alters the Phenotype of Highly Metastatic Osteosarcoma Cells. (24th December 2015) - Mu, Xiaodong; Patel, Stuti; Mektepbayeva, Damel; Mahjoub, Adel; Huard, Johnny; Weiss, Kurt
Abstract : Aldehyde dehydrogenase (ALDH) is a cancer stem cell marker. Retinoic acid has antitumor properties, including the induction of apoptosis and inhibition of proliferation. Retinal, the precursor of retinoic acid, can be oxidized to retinoic acid by dehydrogenases, including ALDH. We hypothesized that retinal could potentially be transformed to retinoic acid with higher efficiency by cancer stem cells, due to the higher ALDH activity. We previously observed that ALDH activity is greater in highly metastatic K7M2 osteosarcoma (OS) cells than in nonmetastatic K12 OS cells. We also demonstrated that ALDH activity correlates with clinical metastases in bone sarcoma patients, suggesting that ALDH may be a therapeutic target specific to cells with high metastatic potential. Our current results demonstrated that retinal preferentially affected the phenotypes of ALDH-high K7M2 cells in contrast to ALDH-low K12 cells, which could be mediated by the more efficient transformation of retinal to retinoic acid by ALDH in K7M2 cells. Retinal treatment of highly metastatic K7M2 cells decreased their proliferation, invasion capacity, and resistance to oxidative stress. Retinal altered the expression of metastasis-related genes. These observations indicate that retinal may be used to specifically target metastatic cancer stem cells in OS.